2011
DOI: 10.1007/s10549-011-1404-7
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide analysis of incidence and outcome of breast cancer in the country of Surinam, during 1994–2003

Abstract: In this study, we describe the incidence, treatment, and outcome of breast cancer (BC) during the period 1994-2003 in the South-American country of Surinam and compare these with those of BC in the Netherlands. Pathology reports and hospital charts from all BC cases diagnosed between 1994 and 2004 were retrieved from Surinam's single pathology laboratory and its five hospitals. Data on demographics, tumor characteristics, treatment, and follow-up were gathered. We compared our data to BC statistics of first ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Several investigators have reported on various aspects of the epidemiology of adult malignancies -particularly carcinomas -in Suriname [24][25][26][27]. Up till now, no comprehensive data are available on the occurrence of cancer in Surinamese newborns, infants, young children, adolescents, and young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have reported on various aspects of the epidemiology of adult malignancies -particularly carcinomas -in Suriname [24][25][26][27]. Up till now, no comprehensive data are available on the occurrence of cancer in Surinamese newborns, infants, young children, adolescents, and young adults.…”
Section: Introductionmentioning
confidence: 99%
“…p  > 0.05. Proportions and CI obesity: Hispanic white (43.5%, 26.5–61.4), Hispanic black (35.6%, 23.0–48.2), nonhispanic black immigrant (44.3%, 37.9–50.7), nonhispanic black USVI-born (38.8%, 29.9–47.7).van Leeuwaarde, 2011 [70]Registry-based/(all)PopulationSuriname/Ethnicity I /Proportions and incidence rates (per 100,000 per year) of breast cancer: Creole (37.2%, 35.7), Maroons (1.9%, 2.2), Hindu (29.4%, 18.2), Javanese (17.9%, 20.8), Chinese (1.9%, not given), mixed (7.4%, 10.1), Dutch (1.4%, not given), other (2.9%, not given). Note these proportions also reflect the ethnography of the general Suriname population.Varona, 2011 [45] (a)Cross-sectional22,85115+PopulationCubaIncome – perception of economic situationAge Alc //Proportions and CI of females consuming alcohol in past 30 days across age group: 15–19 (11.4%, 8.9–13.9), 20–39 (14.6%, 13.2–15.9), 40–59 (9.3%, 8.0–10.5), >59 (2.7%, 1.8–3.6).Education Alc Proportions and CI of females consuming alcohol in past 30 days: primary school (4.8%, 3.8–5.7), middle school (10.7%, 9.4–12.1), high school (13.9%, 12.4–15.4), university (13.2%, 10.8–15.7).Ethnicity Alc Proportions and CI of females consuming alcohol in past 30 days: white (8.2%, 7.3–9.0), mestizo (14.7%, 12.9–16.5), black (14.9%, 12.3–17.6).Income Alc Proportions and CI of females consuming alcohol in past 30 days: excellent (8.4%, 2.3–14.6), good (11.8%, 10.0–13.6), fair (10.2%, 9.2–11.1), poor (9.2%, 7.4–10.9), very poor (10.9%, 7.6–14.1).Marital status Alc Proportions and CI of females consuming alcohol in past 30 days: unmarried (14.1%, 12.3–16.0), married or cohabiting (10.0%, 9.0–10.9), divorced or separated (12.0%, 9.9–14.0), widowed (2.5%, 1.4–3.7).Occupation Alc Proportions and CI of females consuming alcohol in past 30 days: manager (18.8%, 13.8–23.7), administrator (14.7%, 10.5–18.8), upper-level technician (13.1%, 10.1–16.1), middle-level technician (12.6%, 10.0–16.1), labourer (14.0%, 10.5–17.2), service worker (16.0%, 13.2–18.8).

• (a) - Articles are components of larger studies: (Block, [40]) - Grenada Heart Project [100] ; ((Blum, [41]), (Ohene, [44])) - Caribbean Youth Health Survey [101]; (Brathwaite, [47]) - 2001 Bahamas Living Conditions Survey [102] ; ((Nam, [55]), (Kim, [42])) – [Health, Wellbeing and Aging] [103]; (Dubois, [49]) - Jamaica Youth Risk and Resiliency Behaviour Survey of 2007 [104] ; (Ferguson, [50]) - Jamaica Birth Cohort [105] ; (Laborde, [53]) - Behavioral Risk Factor Surveillance System [

…”
Section: Resultsmentioning
confidence: 99%
“…There were 75 inequality relationships reported: 59 on breast cancer risk factors, 13 on breast cancer frequency, and 3 on breast cancer outcomes.
Fig. 2Summary of 75 inequality relationships from 34 articles between a social determinant and review endpoint [4070, 72, 73]. Legend: Age and limited breastfeeding cells do not separate youth and adult samples as the studies have combined these age groups in their samples
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations